Analysis of Diversification Strategy of Yoga Sedana Cooperative Savings Products (KSU) to Reduce Dependence on High-Interest Deposits - Ni luh Putu Wulan Swandewi; Eddy Supriyadinata Gorda (Jurnal Multidisiplin Sahombu, 2025)
Koperasi Serba Usaha (KSU) Yoga Sedana is a microfinance institution that plays an important role in providing savings and loan services to the community. However, the cooperative’s dependence on high-interest deposit products poses financial risks, especially in the event of interest rate fluctuations or simultaneous withdrawals by members. This study aims to analyze the savings product diversification strategies implemented by KSU Yoga Sedana, identify the challenges and opportunities encountered, and assess their impact on the cooperative’s financial stability and member participation. The research method employed is qualitative with a descriptive approach. Primary data were obtained through interviews, observations, and documentation involving the cooperative’s management, managers, and members. Meanwhile, secondary data were collected from financial reports, internal documents, and relevant academic references. Data analysis was carried out through the stages of reduction, presentation, and conclusion drawing to explore diversification strategies and their implications for the cooperative’s financial risk management. The study reveals that over the past five years KSU Yoga Sedana has relied heavily on high-interest deposits, creating liquidity risks during interest rate shifts. Diversification strategies were implemented through products such as flexible term savings, daily savings, and thematic savings. These strategies successfully reduced the proportion of high-interest deposits and increased low-cost funds, thereby lowering dependency risks. The findings confirm that product diversification enhances financial stability and encourages member participation. Overall, diversification proves to be an essential step in strengthening the financial resilience of KSU Yoga Sedana.